Ben Delatour Scout Ranch - miscellaneous - Colorado State Forest Service, compiler (Colorado State University. Libraries, 2014)
Located in: Fort Collins office files. Ben Delatour Scout Ranch miscellaneous documentation for years 2014 to 2016 to include program payment requests, related maps, receipts and reports for a Colorado Forest Restoration Grant, Stevens Fuels Treatment Funds, State Fire Assistance WUI Grant Program, and CAFA/Hazardous Fuels Grant Program.
Keywords: Colorado State Forest Service -- History -- Sources; Forests and forestry--Colorado